Evidence based guidelines for the use of hand-held dynamometry for the assessment of shoulder strength in overhead athletes. - Holt, K.; Charlton, P. (Journal of Australian Strength and Conditioning, 2017)
The purpose of this article is to present a reliable method of assessing the maximal isometric strength of the shoulder internal and external rotator musculature for use in overhead athletes. The rate of shoulder injury and pain is high in athletes participating in overhead sports and shoulder muscle strength and imbalance have been previously reported as modifiable risk factors in these populations. The presented method may be used as part of a pre-participation screening protocol, as a basis for developing a resistance training intervention to address deficits or to assess response to and recovery from imposed training and competition loads over the course of a season.